2008
DOI: 10.1152/jn.90634.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Neurons Switch From Integrators In Vitro to Resonators Under In Vivo-Like Conditions

Abstract: Prescott SA, Ratté S, De Koninck Y, Sejnowski TJ. Pyramidal neurons switch from integrators in vitro to resonators under in vivolike conditions. J Neurophysiol 100: 3030 -3042, 2008. First published October 1, 2008 doi:10.1152/jn.90634.2008. During wakefulness, pyramidal neurons in the intact brain are bombarded by synaptic input that causes tonic depolarization, increased membrane conductance (i.e., shunting), and noisy fluctuations in membrane potential; by comparison, pyramidal neurons in acute slices typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 56 publications
(58 reference statements)
10
164
0
Order By: Relevance
“…7A) because the quenched variability (van Vreeswijk and Sompolinsky, 1998) introduced by each neuron having a different set of presynaptic neurons suffices. Missed and skipped cycles (Glass and Winfree, 1984;Kaplan et al, 1996) are characteristic of the subcritical Hopf bifurcation (Ermentrout, 1996;Rinzel and Ermentrout, 1998;Prescott et al, 2008) underlying type 2 excitability (Hodgkin, 1948;Izhikevich, 2007). Fitzhugh (1976) described a "limiting trajectory" in a model with type 2 excitability, a concept that is very similar to the constant rebound interval after a strong inhibition observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7A) because the quenched variability (van Vreeswijk and Sompolinsky, 1998) introduced by each neuron having a different set of presynaptic neurons suffices. Missed and skipped cycles (Glass and Winfree, 1984;Kaplan et al, 1996) are characteristic of the subcritical Hopf bifurcation (Ermentrout, 1996;Rinzel and Ermentrout, 1998;Prescott et al, 2008) underlying type 2 excitability (Hodgkin, 1948;Izhikevich, 2007). Fitzhugh (1976) described a "limiting trajectory" in a model with type 2 excitability, a concept that is very similar to the constant rebound interval after a strong inhibition observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We are interested here only in PIR mechanisms fast enough that can be engaged by inhibitory postsynaptic potentials (IPSPs) generated at GABA A synapses; for example, removal of sodium channel inactivation. In a type 2 oscillator, the net steady-state current at membrane potentials traversed during the ISI is outward, so pacing can only be maintained when the ISI is traversed quickly enough that the inward current evoked by the after-hyperpolarization can persist (Prescott et al, 2008); this rate sets the lower bound on spiking frequency. Otherwise, the oscillation will stop at the point the inward and outward currents come into balance.…”
Section: Resonant Interneuronsmentioning
confidence: 99%
“…(3) Type 2 neurons respond best to fluctuating inputs around a characteristic frequency, whereas type 1 neurons summate inputs across a broad range of frequencies. Types 1 and 2 neurons have therefore been labeled integrators and resonators, respectively [16,29]. (4) The phase response curve (PRC) differs between types 1 and 2 neurons [35]; near the onset of oscillations, type 1 neurons display a monophasic PRC, whereas type 2 neurons can display biphasic PRCs.…”
Section: Linear Spikementioning
confidence: 99%
“…In particular, it has been shown that the mechanisms of spike generation can be very precise (Mainen & Sejnowski, 1995) under physiological conditions (Boucsein et al, 2011;Konishi et al, 1988;Lestienne, 2001;Prescott et al, 2008). Spike synchronization, with or without oscillations, has been shown to be involved in the so-called binding problem (Engel & Singer, 2001;Singer & Gray, 1995;Singer, 1999;Super et al, 2003).…”
Section: Introductionmentioning
confidence: 99%